2021
DOI: 10.3390/nu13051500
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Vitamin D Deficiency among Young South African Infants: A Birth Cohort Study

Abstract: Early-life vitamin D deficiency is associated with adverse child health outcomes, but the prevalence of vitamin D deficiency and its correlates in infants remains underexplored, particularly in sub-Saharan Africa. We aimed to investigate the prevalence of vitamin D deficiency and its correlates among young infants in South Africa. This study included 744 infants, aged 6–10 weeks from the Drakenstein Child Health Study, a population-based birth cohort. Infants were categorized into distinct categories based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
(57 reference statements)
2
12
0
3
Order By: Relevance
“…The study cohort as well as the subcohort tested for vitamin D has been described previously [ 3 , 14 , 15 ]. Briefly, we enrolled pregnant women between 20 and 28 weeks’ gestation attending antenatal care in Paarl, a periurban setting outside of Cape Town, South Africa.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study cohort as well as the subcohort tested for vitamin D has been described previously [ 3 , 14 , 15 ]. Briefly, we enrolled pregnant women between 20 and 28 weeks’ gestation attending antenatal care in Paarl, a periurban setting outside of Cape Town, South Africa.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected on infant factors relevant to vitamin D and tuberculosis disease risk based on prior studies with this cohort [ 3 , 15 ] as well as the medical literature [ 18 ]. Infant variables included sex, height-for-age z score (HAZ), weight-for-age z score (WAZ), maternal HIV, gestational age, breastfeeding practices in the first year of life, and season of birth.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neonates with younger gestational age tend to suffer from a higher incidence rate, lighter weight, and a higher fatality rate (3). Vitamin D is a fat-soluble steroid derivative that plays very important physiological functions in the human body (4), namely improving the body's absorption of calcium and phosphorus, promoting growth and bone calcification (5), and regulating the body's immune function (6). With more and more in-depth research at home and abroad in recent years, many animal and laboratory studies have found that the lack of vitamin D is also involved in the occurrence of respiratory diseases in children (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%